2007
DOI: 10.1063/1.2735322
|View full text |Cite
|
Sign up to set email alerts
|

G Br 6 NL : A generalized Born method for accurately reproducing solvation energy of the nonlinear Poisson-Boltzmann equation

Abstract: The nonlinear Poisson-Boltzmann (NLPB) equation can provide accurate modeling of electrostatic effects for nucleic acids and highly charged proteins. Generalized Born methods have been developed to mimic the linearized Poisson-Boltzmann (LPB) equation at substantially reduced cost. The computer time for solving the NLPB equation is approximately fivefold longer than for the LPB equation, thus presenting an even greater obstacle. Here we present the first generalized Born method, GBr(6)NL, for mimicking the NLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 44 publications
(43 reference statements)
0
47
0
Order By: Relevance
“…However, the solvation part calculated by solving the nonlinear PB equation is not decomposable into contributions of individual atoms. However, we showed that the solvation free energy of the nonlinear PB equation can be reproduced well by a generalized Born (GB) method (38,39). The GB solvation free energy consists of one-body and pair contributions (40).…”
Section: Generation Of Transient-complex Ensemble and Calculation Of mentioning
confidence: 99%
“…However, the solvation part calculated by solving the nonlinear PB equation is not decomposable into contributions of individual atoms. However, we showed that the solvation free energy of the nonlinear PB equation can be reproduced well by a generalized Born (GB) method (38,39). The GB solvation free energy consists of one-body and pair contributions (40).…”
Section: Generation Of Transient-complex Ensemble and Calculation Of mentioning
confidence: 99%
“…The speed with which a model can be calculated then offers a major constraint, and it is desirable to have approximations. The Generalized-Born (GB) model [214,217,218] approximates the local-response Poisson or Poisson–Boltzmann models quickly, and is widely used in MD simulations. However, semi-empirical approximation schemes do not necessarily illustrate how more advanced underlying theories can be approximated.…”
Section: Opportunitiesmentioning
confidence: 99%
“…4144 However, the accuracy of MD simulations is limited by the accuracy of the ion-dependent force field as well as the completeness of the sampling for the ions and water molecules, 34 As a result, accurate calculations require significant computer resources and exceedingly long computer time even for small RNAs. The classical Counterion Condensation (CC) theory 45 and the (nonlinear) Poisson-Boltzmann (NLPB) theory 4651 are simple yet useful theories for the prediction of the ion effects. However, both theories ignore ion correlation and ion fluctuations, two potentially important effects for ions around nucleic acids.…”
Section: Introductionmentioning
confidence: 99%